اسماء رجال کے تناظر میں اعمش کی ثقاہت پر مختلف آراء کا تجزیاتی مطالعہ: Analytical Study of Different Opinions on the Trustworthiness of Al-A’mash in the Context of Asma’ al-Rijal - Hāfiz Muḥammad Imrān (International Research Journal of Arabic and Islamic Studies, 2024)
This study aims to analyze the differing views on the reliability (thiqat) of Sulayman ibn Mihran, known as Al-A’mash, within the framework of Asma' al-Rijal (the science of evaluating narrators of Hadith). Al-A’mash is a prominent figure in Hadith narration, and scholars have expressed varying opinions regarding his reliability. This research investigates these opinions by comparing the views of classical Hadith scholars, weighing the strengths and weaknesses of their arguments. By doing so, it provides a comprehensive understanding of Al-A’mash's standing in the science of Hadith narration and assesses his contribution to the transmission of Islamic knowledge.